2010
DOI: 10.1177/1469787410365655
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative approach to higher education induction

Abstract: Success in higher education is often measured by one's ability to conduct research, effectively disseminate findings, and competently teach in a collegiate setting. These measures are not entirely developed during doctoral school, let alone as a classroom teacher. In order to increase the likelihood of success at the higher education level, several newly hired faculty members at a four-year university created the new faculty guild by which they would share scholarly progress, insight into effective teaching st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
(23 reference statements)
1
14
0
Order By: Relevance
“…Much of the literature has focused on the success of the person being mentored as an indicator of effectiveness in dealing with the varying degree of pressure placed on junior academic staff (Ortlieb, Biddix, and Doepker, 2010). As far as the mentor is concerned, the expectation is that he/she knows how to function in the role based on an assumed prior mentoring relationship.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
“…Much of the literature has focused on the success of the person being mentored as an indicator of effectiveness in dealing with the varying degree of pressure placed on junior academic staff (Ortlieb, Biddix, and Doepker, 2010). As far as the mentor is concerned, the expectation is that he/she knows how to function in the role based on an assumed prior mentoring relationship.…”
Section: International Journal Of Learning and Developmentmentioning
confidence: 99%
“…Bengtsson, 1993). Earlier studies (Danielsson et al, 2009;Ortlieb et al, 2010) have shown that the teacher's own learning process is likely in need of collective support. A teacher group with an open and explorative attitude to the members' teaching practices can be viewed as necessary in all higher education.…”
Section: Discussionmentioning
confidence: 99%
“…One way of supporting individual teachers in their teaching is to create opportunities for collegial learning, thereby building a common arena for the teachers' didactic knowledge development (e.g. Hemer, 2014;Ortlieb, Biddix, & Doepker, 2010). Collegial support for the development of supervisory skills has proven to have positive effects on both professional and personal growth (Danielsson, Sundin-Andersson, Hov, & Athlin, 2009).…”
Section: University Teachers' Pedagogical Competence and Learningmentioning
confidence: 99%
“…Faculty Development Program is not just restricted to research and teaching methods but also a good character and personality. Thus taking into consideration this aspect Ortlieb, Biddix, and Doepker (2010), have argued that support for faculty should include developing faculty communities that 1) foster positive relationships with other faculty members, 2) encourage partnerships for research, 3) provide a network of support, 4) encourage critical reflection, and 5) offer monthly support groups to help faculty members develop into their roles. Faculties should also develop themselves to teach better, communicate to the students, and aim to maintain a smooth relationship with the students.…”
Section: Review Of Literaturementioning
confidence: 99%